1995
DOI: 10.1042/bj3080641
|View full text |Cite
|
Sign up to set email alerts
|

The haem b558 component of the cytochrome bd quinol oxidase complex from Escherichia coli has histidine-methionine axial ligation

Abstract: The cytochrome bd ubiquinol oxidase from Escherichia coli is induced when the bacteria are cultured under microaerophilic or low-aeration conditions. This membrane-bound respiratory oxidase catalyses the two-electron oxidation of ubiquinol and the four-electron reduction of dioxygen to water. The oxidase contains three haem prosthetic groups: haem b558, haem b595 and haem d. Haem d is the oxygen binding site, and it is likely that haem d and b595 form a bimetallic site in the enzyme. Haem b558 has been previou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(42 citation statements)
references
References 35 publications
4
38
0
Order By: Relevance
“…A69611). Three of the four axial ligands to the irons of the three hemes have been identified as His-19, His-186, and Met-393 of CydA (subunit I) in the E. coli cytochrome bd oxidase (25,40,68,69). The corresponding residues are conserved as His-18, His-183, and Met-333 in M. thermoacetica CydA.…”
Section: Resultsmentioning
confidence: 99%
“…A69611). Three of the four axial ligands to the irons of the three hemes have been identified as His-19, His-186, and Met-393 of CydA (subunit I) in the E. coli cytochrome bd oxidase (25,40,68,69). The corresponding residues are conserved as His-18, His-183, and Met-333 in M. thermoacetica CydA.…”
Section: Resultsmentioning
confidence: 99%
“…The small isolated peak at g ϭ 3.47 is the g z feature of the second limiting type of low-spin ferric heme EPR, a "large g max " spectrum for which the g y and g x features are broad and often not detected (42). Again, these features are not unique to any one pair of axial ligands, and there are a number of examples in the literature of such spectra arising from both His/His and His/Met coordination (43)(44)(45).…”
Section: Fig 2 Multiple Sequence Alignments Of Ccoo and Ccopmentioning
confidence: 99%
“…The horizontal bar indicates the periplasmic Q-loop of CydA, which contains the proposed quinol-binding site, and the corresponding shorter region in CioA. of spectroscopic methods Fang et al, 1989;Jiang et al, 1993;Spinner et al, 1995). These studies have identified His-186 and Met-393 of CydA as the ligands to haem b 558 .…”
Section: Figmentioning
confidence: 99%